Implementation issues in clock synchronization - Beck, Micah; Srikanth, T. K.; Toueg, Sam (1986)
We present some results from an experimental implementation of a recent clocks synchronization algorithm. This algorithm was designed to overcome arbitrary processor failures, and to achieve optimal accuracy, i.e., the accuracy of synchronized clocks (with respect to real time) is as good as that specified for the underlying hardware clocks. Our system was implemented on a set of workstations on a local area braodcast network. Initial results indicate that this algorithm can form the basis of an accurate, reliable, and practical distributed time service.
Keywords: Fault-tolerant computing; Synchronization